41.1: Invited Paper: Efficient pre‐treatment for improving the via hole profile in 4‐mask process TFT architecture. (4th October 2019) - Zhen, Liu; An-Thung, Cho; Hejing, Zhang; Fengyun, Yang; Kaijun, Liu; Qionghua, Mo; Chao, Wei; Wanfei, Yong; James, Hsu
Abstract : Ways to solve the passivation layer undercut in via hole were described in detail. By tuning the pretreatment before the passivation layer deposition, the passivation layer undercut in via hole was solved efficiently without any other side effects. Different from changing dry etching process parameters, we increasing the adhesion of the interface between metal layer and passivation layer to overcome undercut issue.